Effects of oral health-related quality of life on total mortality: a prospective cohort study - Nishiki Arimoto; Rumi Nishimura; Teruo Kobayashi; Mayuka Asaeda; Toru Naito; Masaaki Kojima; Osami Umemura; Makoto Yokota; Nobuhiro Hanada; Takashi Kawamura; Kenji Wakai; Mariko Naito (BMC, 2023)
Abstract Background The effects of oral health on mortality have been reported; however, the association between mortality and Oral Health-Related Quality of Life (OHQOL) is unknown. We investigated the effect of OHQOL on total mortality in a cohort consisting of dentists. Methods In this cohort study, we analyzed data from the Longitudinal Evaluation of Multi-phasic, Odonatological and Nutritional Associations in Dentists study. We conducted a baseline survey of general and oral health factors. We called for 31,178 participants and collected responses from 10,256 participants. We followed up with 10,114 participants (mean age ± standard deviation, 52.4 ± 12.1 years; females, 8.9%) for 7.7 years, until March 2014, to determine the average total mortality. OHQOL was assessed using the General Oral Health Assessment Index (GOHAI). The total score was divided into quartiles (Q1 ≤ 51.6, Q2 = 51.7-56.7, Q3 = 56.8-59.9, and Q4 = 60.0), with higher GOHAI scores indicating better OHQOL (score range, 12-60). The association between OHQOL and total mortality was analyzed using the Cox proportional hazards model. Results We documented 460 deaths. Males with low GOHAI scores possessed a remarkably high risk of total mortality. The multivariate adjusted-hazard ratios (aHRs), were 1.93 (95% confidence interval [CI], 1.07 − 3.48) for Q1, 1.69 (95% CI, 0.90 − 3.17) for Q2, and 0.65 (95% CI, 0.29 − 1.46) for Q3, relative to Q4 (trend p = 0.001). The aHRs in the multivariate model with all background variables were 1.69 (95% CI, 1.15-2.46) for Q1, 1.53 (95% CI, 1.04-2.27) for Q2, and 1.09 (95% CI, 0.71-1.70) for Q3, relative to Q4 (trend p = 0.001). In females, there was no significant association between the quartiles, in both the multivariate-adjusted model (trend p = 0.52) and multivariate-adjusted model with all background variables (trend p = 0.79). Conclusions A lower OHQOL indicated an increased risk of total mortality in dentists. OHQOL may be used as an indicator for selecting treatment plans and personalized care interventions, thus contributing to increased healthy life expectancy. Trial registration Aichi Cancer Center, Nagoya University Graduate School of Medicine, and Hiroshima University (Approval numbers: 33, 632-3, 8-21, and E2019-1603).